Flame-retardant wave-absorbing material based on expanded polystyrene and preparation method thereof
By compounding iron tetraoxide with graphene, and curing the phenolic resin through azide-alkyne click chemical reaction, forming a wave absorber, and introducing a ring triphosphazene structure, the problem of insufficient flame retardancy of existing wave absorbing materials is solved, and efficient flame retardant and wave absorbing properties are achieved.
Patent Information
- Application Number
- CN202510413117.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-03
AI Technical Summary
The existing wave absorbing materials have shortcomings in flame retardancy, especially the flame retardant performance of the resin bonded part needs to be improved.
The magnetic loss absorbing material ferric oxide is composited with the resistance loss absorbing material graphene by solvothermal method to prepare the graphene/ferric oxide composite material, and the azide-alkyne-based linear phenolic resin is cured on the surface of the graphene/ferric oxide composite material through azide-alkyne click chemical reaction to form a wave absorber. Meanwhile, a hexa(p-aminophenoxy)cyclotriphosphazene structure was introduced to improve flame retardant properties.
The excellent flame retardant and wave absorbing properties of wave absorbing materials are achieved, the thermal stability and dispersion of the materials are improved, and its application performance in electromagnetic shielding and radiation protection is enhanced.
Smart Images

Figure CN119910975A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of layered composite materials, and in particular to a flame-retardant wave-absorbing material based on foamed polystyrene and a preparation method thereof. Background Art
[0002] Absorbing materials, also known as radar absorbing materials, refer to a type of material that can absorb and attenuate incident electromagnetic waves, convert electromagnetic energy into other forms of energy and consume it, or make electromagnetic waves disappear through interference. Electromagnetic shielding technology can relatively simply and effectively prevent electromagnetic waves from leaking out and avoid electromagnetic radiation, but most shielding measures only reflect electromagnetic waves and do not fundamentally attenuate them, which can easily cause secondary pollution of electromagnetic radiation. Absorbing materials can absorb and consume the energy of incident electromagnetic waves inside the material, effectively reducing the energy of reflected electromagnetic waves.
[0003] According to the molding process, the absorbing material can be divided into a coating type absorbing material and a structural type absorbing material; the foam sandwich structure absorbing composite material is a structural type absorbing material, which uses advanced composite materials as a carrier and organically combines the absorbing material with the foam sandwich material, and is a new type of absorbing material. The prior art, such as Chinese patent application CN114670526A, discloses an absorbing honeycomb core material and an absorbing honeycomb core sandwich structure, which includes a honeycomb matrix, a resin bonding part and an absorbing material, and the metalized hollow glass microbeads of the absorbing material are fixed on the honeycomb matrix through resin bonding, thereby improving the electromagnetic wave absorption rate of the material. However, the flame retardancy of the resin bonding part needs to be improved. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a flame retardant wave absorbing material based on expanded polystyrene and a preparation method thereof, wherein the prepared composite material has excellent flame retardant and wave absorbing properties.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a flame retardant wave absorbing material based on foamed polystyrene comprises the following steps: Step (1), mixing graphene, ferric chloride hexahydrate, sodium acetate and a solvent, dispersing by ultrasonication, reacting, and after the reaction is completed, cooling, centrifuging, filtering, washing and drying to obtain a graphene / ferrosoferric oxide composite material; The 3-(azidopropyl)triethoxysilane, the graphene / ferroferric oxide composite material and toluene are mixed and reacted, and after the reaction is completed, the mixture is filtered, washed and dried to obtain the azido graphene / ferroferric oxide composite material; The graphene azide / ferrosilicate composite material is mixed with N,N-dimethylformamide, ultrasonically dispersed, and propargyl linear phenolic resin is added, and pentamethyldiethyltriamine and cuprous iodide are added in a nitrogen atmosphere to react. After the reaction is completed, centrifugation, filtration, and drying are performed to obtain a wave absorbing agent; Step (2), mixing and stirring phenolic resin, flame retardant functionalized phenolic resin, ammonium polyphosphate, and absorbent to obtain a flame retardant coating resin; The flame retardant functionalized phenolic resin is prepared by the following steps: Phenol, sodium hydroxide, the first portion of paraformaldehyde and water are mixed, hexa(p-aminophenoxy)cyclotriphosphazene is added, reacted, after the reaction is completed, the second portion of paraformaldehyde is added, the reaction is continued, after the reaction is completed, the third portion of paraformaldehyde is added, the reaction is repeated, after the reaction is completed, the mixture is cooled to room temperature to obtain a modified phenolic resin; The modified phenolic resin and N,N-dimethylacetamide are mixed and dissolved, 4-nitrophthalonitrile and a catalyst potassium carbonate are added, and the mixture is reacted. After the reaction is completed, the mixture is cooled and purified to obtain a flame-retardant functionalized phenolic resin. Step (3), pre-foaming the expandable polystyrene beads, and after the pre-foaming is completed, aging to obtain pre-foamed polystyrene beads; The pre-foamed polystyrene beads are mixed with a flame-retardant coating resin, stirred, dried, placed in a mold after drying, and foamed a second time. After the second foaming is completed, cooled and dried to obtain a foamed polystyrene-based composite material; Step (4), using the expanded polystyrene-based composite material as the middle layer, the glass fiber prepreg as the upper layer, and the carbon fiber material as the lower layer, and laminating and compounding them in the order of upper layer, middle layer, and lower layer, and hot pressing to obtain a flame-retardant absorbing material based on expanded polystyrene.
[0006] Preferably, in step (1), the mass ratio of graphene, ferric chloride hexahydrate, sodium acetate and solvent is 0.03:2-2.1:37.5-38:835; when preparing the graphene / ferrosoferric oxide composite material, the reaction conditions are: reacting at 200°C for 8-10 hours.
[0007] Furthermore, the solvent is prepared by mixing ethylene glycol and diethylene glycol in a mass ratio of 415-420:415-420.
[0008] Preferably, in step (1), the mass ratio of 3-(azidopropyl)triethoxysilane, graphene / ferroferric oxide composite material, and toluene is 0.18-0.2:0.1:100-130; when preparing the azidographene / ferroferric oxide composite material, the reaction conditions are: reacting in a light-proof environment at a temperature of 70-80°C for 24-30h.
[0009] Preferably, in step (1), the mass ratio of the graphene azide / ferrosiron tetroxide composite material, N,N-dimethylformamide, propargyl linear phenolic resin, pentamethyldiethyltriamine, and cuprous iodide is 1:100-130:2.8-3:0.03:0.28; when preparing the absorber, the reaction conditions are: reacting at a temperature of 25-30°C for 24-26h.
[0010] Preferably, in step (1), the propargylating phenolic novolac resin comprises the following steps to prepare the resin: The linear phenolic resin, sodium hydroxide, 3-bromopropyne, water and butanone are uniformly mixed, a catalyst is added, and the mixture is reacted. After the reaction is completed, the mixture is purified to obtain the propargylated linear phenolic resin.
[0011] Preferably, in the step (1) of preparing the propargylated phenolic resin, the mass ratio of phenolic resin, sodium hydroxide, 3-bromopropyne, water, butanone and catalyst is 10:3-3.2:9-9.2:50-60:50-60:0.1-0.14; and the reaction conditions are: stirring the reaction at 70-80°C for 8-10h.
[0012] Furthermore, the purification operation includes: after the reaction is completed, a crude reaction product is obtained, water of 3-4 times the mass of the crude reaction product is added for washing, an organic phase is taken, the solvent is removed by rotary evaporation, and the product is dried at a temperature of 100-120° C. for 10-14 hours.
[0013] Furthermore, the catalyst is triethylbenzyl ammonium chloride.
[0014] Preferably, in step (2), the mass ratio of phenolic resin, flame retardant functionalized phenolic resin, ammonium polyphosphate and absorber is 50-60:40-50:5-6:20-25.
[0015] Preferably, in the step (2) of preparing the flame-retardant functionalized phenolic resin, the mass ratio of phenol, sodium hydroxide, water, paraformaldehyde and hexa(p-aminophenoxy)cyclotriphosphazene is 92-94:0.4-0.5:6:40-46:8-10; the paraformaldehyde comprises a first part of paraformaldehyde, a second part of paraformaldehyde and a third part of paraformaldehyde, and the mass ratio of the first part of paraformaldehyde, the second part of paraformaldehyde and the third part of paraformaldehyde is 1:1:1; in the preparation of the modified phenolic resin, the reaction conditions are: reacting at a temperature of 80-90°C for 1-2h, continuing to react at a temperature of 80-90°C for 0.5-1h, and reacting again at a temperature of 80-90°C for 1-1.5h.
[0016] Preferably, in the step (2), when preparing the flame retardant functionalized phenolic resin, the mass ratio of the modified phenolic resin, 4-nitrophthalonitrile, and the catalyst potassium carbonate is 60:12-14:15-16; when preparing the flame retardant functionalized phenolic resin, the reaction conditions are: reacting at a temperature of 75-80° C. for 16-18 hours.
[0017] Preferably, the purification operation includes: filtering, taking the filtrate, adding 0.01 mol / L aqueous hydrogen chloride solution to neutralize to neutrality to obtain a crude reaction product, adding 8-10 times the mass of the crude reaction product of butanone for extraction, taking the organic phase, rotary evaporating to remove the solvent, and drying at 50-60°C for 8-10 hours.
[0018] Preferably, in step (3), the pre-foaming conditions are: pre-foaming in water vapor with a vapor pressure of 0.4-0.5 MPa and a temperature of 100°C for 50-55 seconds; the aging conditions are: aging at room temperature for 12-20 hours; the mass ratio of the pre-foamed polystyrene beads to the flame-retardant coating resin is 25:15-18; the secondary foaming conditions are: secondary foaming in water vapor with a vapor pressure of 0.3-0.4 MPa and a temperature of 120-130°C for 3-3.5 minutes; and the thickness of the foamed polystyrene-based composite material is 40-50 mm.
[0019] Preferably, in step (4), the hot pressing conditions are: hot pressing at a pressure of 0.15-0.2 MPa and a temperature of 135-145° C. for 2-2.5 h.
[0020] Preferably, a flame retardant absorbing material based on expanded polystyrene is prepared by the method for preparing a flame retardant absorbing material based on expanded polystyrene as described above.
[0021] Compared with the prior art, the present invention has the following beneficial effects: The invention uses a solvothermal method to compound a magnetic loss type wave absorbing material, ferroferric oxide, and a resistive loss type wave absorbing material, graphene, to prepare a graphene / ferroferric oxide composite material with excellent wave absorbing performance, and then uses 3-(azidopropyl)triethoxysilane to perform surface modification on the composite material to obtain an azidized graphene / ferroferric oxide composite material with an azide group on the surface, and then reacts the composite material with a propargyl linear phenolic resin under the action of a catalyst to undergo an azide-alkyne click chemical reaction, so that the linear phenolic resin structure is solidified on the surface of the graphene / ferroferric oxide composite material to obtain a wave absorbing agent; Among them, the propargylated phenolic resin is prepared by reacting the phenolic resin with 3-bromopropyne, and will form a nitrogen-containing triazole ring structure after reacting with the graphene azide / ferroferric oxide composite material. The introduction of the propargylated phenolic resin not only improves the dispersibility of the absorber in the flame-retardant coating resin matrix, but also further improves the thermal stability and flame retardancy of the matrix.
[0022] The invention introduces hexa(p-aminophenoxy)cyclotriphosphazene containing a cyclotriphosphazene flame retardant structure into a phenolic resin, and a dehydration condensation reaction occurs between an amino group and an aldehyde group and a hydroxymethyl group, while introducing nitrogen and phosphorus elements into the phenolic resin, thereby increasing the crosslinking density of the phenolic resin. The prepared modified phenolic resin further undergoes an etherification reaction with 4-nitrophthalonitrile, and a phthalonitrile structure with good flame retardancy and heat resistance is introduced into the modified phenolic resin. The prepared flame retardant functionalized phenolic resin has excellent flame retardancy, and the flame retardant functionalized phenolic resin is mixed with a phenolic resin, ammonium polyphosphate and a wave absorbing agent to prepare a flame retardant coating resin. The present invention adopts a resin coating method, pre-foams expandable polystyrene beads and mixes them with a flame-retardant coating resin, so that the flame-retardant coating resin is used as a binder to uniformly coat the surface of the pre-foamed polystyrene beads, and obtains a foamed polystyrene-based composite material after secondary foaming by molding. The foamed polystyrene-based composite material is used as an absorbing layer, and a glass fiber prepreg with good flame retardancy and good wave transmission performance and a carbon fiber material with high reflection performance are hot-pressed and bonded on the upper and lower parts, respectively, to obtain a flame-retardant absorbing material with a three-layer composite structure. As a structural absorbing material, the material has excellent flame retardancy and absorbing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a process flow chart for preparing a flame-retardant wave-absorbing material based on expanded polystyrene in the present invention; Figure 2 It is a schematic structural diagram of the flame-retardant wave-absorbing material based on expanded polystyrene prepared in the present invention; Figure 3 It is a bar graph of the limiting oxygen index of samples 1-7 in the flame retardant performance test of the present invention; In the figure: 1. Upper layer; 2. Middle layer; 3. Lower layer. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] Example 1 This embodiment discloses a method for preparing a flame retardant wave absorbing material based on foamed polystyrene, comprising the following steps: Step (1), mixing graphene, ferric chloride hexahydrate, sodium acetate, ethylene glycol, and diethylene glycol in a mass ratio of 0.03:2.1:37.5:415:420, ultrasonically dispersing for 15 minutes, reacting at 200°C for 8 hours, cooling to room temperature after the reaction, centrifuging, filtering, taking the filter cake, adding water 5 times the mass of the filter cake for washing, and drying at 40°C for 8 hours to obtain a graphene / ferrosoferric oxide composite material; 3-(azidopropyl)triethoxysilane, graphene / ferroferric oxide composite material, and toluene were mixed in a mass ratio of 0.19:0.1:120, reacted in a light-proof environment at 75°C for 26 hours, filtered after the reaction, and the filter cake was taken, washed with ethanol 6 times the mass of the filter cake, and dried at 55°C for 10 hours to obtain an azido graphene / ferroferric oxide composite material; The graphene azidite / ferrosilicate composite material was mixed with N,N-dimethylformamide, ultrasonically dispersed for 5 minutes, and propargylated linear phenolic resin was added. The ligand pentamethyldiethyltriamine and the catalyst cuprous iodide were added in a nitrogen atmosphere. The mass ratio of the graphene azidite / ferrosilicate composite material, N,N-dimethylformamide, propargylated linear phenolic resin, pentamethyldiethyltriamine, and the catalyst cuprous iodide was 1:100:2.8:0.03:0.28. The reaction was carried out at 25°C for 26 hours. After the reaction was completed, the mixture was centrifuged and filtered. The filter cake was taken and dried at 50°C for 24 hours in a light-proof environment to obtain a wave absorbing agent. Wherein, the propargyl phenolic resin is prepared by the following steps: Mix the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water and butanone evenly, add the catalyst triethylbenzyl ammonium chloride, the mass ratio of the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water, butanone and the catalyst is 10:3:9:50:60:0.1, stir and react at 70°C for 10h, after the reaction is completed, obtain a crude reaction product, add water 3 times the mass of the crude reaction product for washing, take the organic phase, remove the solvent by rotary evaporation, and dry at 100°C for 14h to obtain the propargylated linear phenolic resin; Step (2), mixing phenolic resin, flame retardant functionalized phenolic resin, ammonium polyphosphate, and absorber in a mass ratio of 60:40:5:20, and stirring at a speed of 400 r / min for 6 minutes to obtain a flame retardant coating resin; The flame retardant functionalized phenolic resin is prepared by the following steps: Divide paraformaldehyde into three parts, wherein the mass ratio of the first part of paraformaldehyde, the second part of paraformaldehyde and the third part of paraformaldehyde is 1:1:1; mix phenol, sodium hydroxide, the first part of paraformaldehyde and water, add hexa(p-aminophenoxy)cyclotriphosphazene, react at 85°C for 2h, add the second part of paraformaldehyde after the reaction, continue to react at 85°C for 1h, add the third part of paraformaldehyde after the reaction, react again at 85°C for 1h, cool to room temperature after the reaction, and obtain a modified phenolic resin; the mass ratio of phenol, sodium hydroxide, water, paraformaldehyde and hexa(p-aminophenoxy)cyclotriphosphazene is 93:0.45:6:44:9; The modified phenolic resin and solvent N,N-dimethylacetamide are mixed and dissolved in a mass ratio of 1:4, 4-nitrophthalonitrile and catalyst potassium carbonate are added, and the mass ratio of the modified phenolic resin, 4-nitrophthalonitrile and catalyst potassium carbonate is 60:12:15. The mixture is reacted at 75°C for 18 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, and the filtrate is taken. A 0.01 mol / L aqueous solution of hydrogen chloride is added to neutralize the mixture to obtain a crude reaction product. Butanone in an amount of 8 times the mass of the crude reaction product is added for extraction. The organic phase is taken, the solvent is removed by rotary evaporation, and the mixture is dried at 50°C for 10 hours to obtain a flame-retardant functionalized phenolic resin. Step (3), placing the expandable polystyrene beads in water vapor, pre-foaming them in water vapor with a vapor pressure of 0.4 MPa at a temperature of 100° C. for 50 seconds, and after the pre-foaming is completed, aging them at room temperature for 12 hours to obtain pre-foamed polystyrene beads; The pre-foamed polystyrene beads and the flame-retardant coating resin were mixed and stirred at a mass ratio of 25:15 for 10 minutes, so that the flame-retardant coating resin was evenly coated on the surface of the pre-foamed polystyrene beads, dried at 50°C for 15 minutes, placed in a mold after drying, and secondary foamed for 3.5 minutes at 120°C in water vapor with a vapor pressure of 0.3MPa. After the secondary foaming, cooled to room temperature, dried at 50°C for 30 hours, and obtained a foamed polystyrene-based composite material with a thickness of 40mm; Step (4), using the expanded polystyrene-based composite material as the middle layer, the glass fiber prepreg as the upper layer, and the carbon fiber material as the lower layer, stacking and compounding in the order of upper layer, middle layer, and lower layer, and hot pressing at a pressure of 0.15 MPa and a temperature of 135° C. for 2.5 hours to obtain a flame retardant absorbing material based on expanded polystyrene.
[0026] Example 2 This embodiment discloses a method for preparing a flame retardant wave absorbing material based on foamed polystyrene, comprising the following steps: Step (1), mixing the graphene azidite / ferrous oxide composite material with N,N-dimethylformamide, ultrasonically dispersing for 5 minutes, adding propargyl linear phenolic resin, and then adding ligand pentamethyldiethyltriamine and catalyst cuprous iodide in a nitrogen atmosphere, wherein the mass ratio of the graphene azidite / ferrous oxide composite material, N,N-dimethylformamide, propargyl linear phenolic resin, pentamethyldiethyltriamine, and catalyst cuprous iodide is 0.3:110:2.85:0.03:0.28, reacting at 25°C for 26 hours, and after the reaction is completed, centrifuging, filtering, taking the filter cake, and drying it at 55°C for 20 hours in a light-proof environment to obtain a wave absorbing agent; The preparation of the graphene azide / ferroferric oxide composite material is the same as that in Example 1; the propargyl linear phenolic resin is prepared by the following steps: Mix the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water and butanone evenly, add the catalyst triethylbenzyl ammonium chloride, the mass ratio of the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water, butanone and the catalyst is 10:3.05:9.05:53:57:0.11, stir and react at 70°C for 10h, after the reaction is completed, obtain a crude reaction product, add water 3 times the mass of the crude reaction product for washing, take the organic phase, remove the solvent by rotary evaporation, and dry at 110°C for 12h to obtain the propargylated linear phenolic resin; Step (2), mixing phenolic resin, flame retardant functionalized phenolic resin, ammonium polyphosphate, and absorber in a mass ratio of 53:47:5.3:22, and stirring at a speed of 400 r / min for 8 minutes to obtain a flame retardant coating resin; The flame retardant functionalized phenolic resin is prepared by the following steps: The preparation of the modified phenolic resin is the same as that in Example 1; the modified phenolic resin and the solvent N,N-dimethylacetamide are mixed and dissolved in a mass ratio of 1:4, 4-nitrophthalonitrile and the catalyst potassium carbonate are added, and the mass ratio of the modified phenolic resin, 4-nitrophthalonitrile and the catalyst potassium carbonate is 60:12.5:15.3, and the mixture is reacted at 75°C for 18 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, and the filtrate is taken, and a 0.01 mol / L aqueous solution of hydrogen chloride is added to neutralize the mixture to neutrality to obtain a crude reaction product, and 8 times the mass of butanone of the crude reaction product is added for extraction, and the organic phase is taken, the solvent is removed by rotary evaporation, and the mixture is dried at 55°C for 8 hours to obtain a flame retardant functionalized phenolic resin; Step (3), placing the expandable polystyrene beads in water vapor, pre-foaming them in water vapor with a vapor pressure of 0.45 MPa at a temperature of 100° C. for 50 seconds, and after the pre-foaming is completed, aging them at room temperature for 16 hours to obtain pre-foamed polystyrene beads; The pre-foamed polystyrene beads and the flame-retardant coating resin were mixed and stirred at a mass ratio of 25:16 for 10 minutes, so that the flame-retardant coating resin was evenly coated on the surface of the pre-foamed polystyrene beads, dried at 55°C for 10 minutes, placed in a mold after drying, and secondary foamed for 3.5 minutes at 120°C in water vapor with a vapor pressure of 0.3MPa. After the secondary foaming, cooled to room temperature, dried at 55°C for 26 hours, and obtained a foamed polystyrene-based composite material with a thickness of 43mm; Step (4), using the expanded polystyrene-based composite material as the middle layer, the glass fiber prepreg as the upper layer, and the carbon fiber material as the lower layer, stacking and compounding in the order of upper layer, middle layer, and lower layer, and hot pressing at a pressure of 0.18 MPa and a temperature of 135° C. for 2.5 hours to obtain a flame retardant absorbing material based on expanded polystyrene.
[0027] Example 3 This embodiment discloses a method for preparing a flame retardant wave absorbing material based on foamed polystyrene, comprising the following steps: Step (1), mixing the graphene azidite / ferrous oxide composite material with N,N-dimethylformamide, ultrasonically dispersing for 5 minutes, adding propargyl linear phenolic resin, and then adding ligand pentamethyldiethyltriamine and catalyst cuprous iodide in a nitrogen atmosphere, wherein the mass ratio of the graphene azidite / ferrous oxide composite material, N,N-dimethylformamide, propargyl linear phenolic resin, pentamethyldiethyltriamine, and catalyst cuprous iodide is 1:115:2.9:0.03:0.28, reacting at 28°C for 25 hours, centrifuging, filtering, taking the filter cake, and drying it at 55°C for 20 hours in a light-proof environment to obtain a wave absorbing agent; The preparation of the graphene azide / ferroferric oxide composite material is the same as that in Example 1; the propargyl linear phenolic resin is prepared by the following steps: Mix the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water and butanone evenly, add the catalyst triethylbenzyl ammonium chloride, the mass ratio of the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water, butanone and the catalyst is 10:3.1:9.1:55:55:0.12, stir and react at 75°C for 9h, after the reaction is completed, obtain a crude reaction product, add water 3 times the mass of the crude reaction product for washing, take the organic phase, remove the solvent by rotary evaporation, and dry at 110°C for 12h to obtain the propargylated linear phenolic resin; Step (2), mixing phenolic resin, flame retardant functionalized phenolic resin, ammonium polyphosphate, and absorber in a mass ratio of 55:45:5.5:23, and stirring at a speed of 400 r / min for 8 minutes to obtain a flame retardant coating resin; The flame retardant functionalized phenolic resin is prepared by the following steps: The preparation of the modified phenolic resin is the same as that in Example 1; the modified phenolic resin and the solvent N,N-dimethylacetamide are mixed and dissolved in a mass ratio of 1:4.5, 4-nitrophthalonitrile and the catalyst potassium carbonate are added, and the mass ratio of the modified phenolic resin, 4-nitrophthalonitrile and the catalyst potassium carbonate is 60:13:15.5, and the mixture is reacted at 78°C for 17 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, and the filtrate is taken, and a 0.01 mol / L aqueous solution of hydrogen chloride is added to neutralize the mixture to neutrality to obtain a crude reaction product, and 8 times the mass of butanone of the crude reaction product is added for extraction, and the organic phase is taken, the solvent is removed by rotary evaporation, and the mixture is dried at 55°C for 8 hours to obtain a flame retardant functionalized phenolic resin; Step (3), placing the expandable polystyrene beads in water vapor, pre-foaming them in water vapor with a vapor pressure of 0.45 MPa at a temperature of 100° C. for 53 seconds, and after the pre-foaming is completed, aging them at room temperature for 16 hours to obtain pre-foamed polystyrene beads; The pre-foamed polystyrene beads and the flame-retardant coating resin were mixed and stirred at a mass ratio of 25:16.5 for 13 minutes, so that the flame-retardant coating resin was evenly coated on the surface of the pre-foamed polystyrene beads, dried at 55°C for 10 minutes, placed in a mold after drying, and secondary foamed for 3.3 minutes at 125°C in water vapor with a vapor pressure of 0.35MPa. After the secondary foaming, cooled to room temperature, dried at 55°C for 26 hours, and obtained a foamed polystyrene-based composite material with a thickness of 45mm; Step (4), using the expanded polystyrene-based composite material as the middle layer, the glass fiber prepreg as the upper layer, and the carbon fiber material as the lower layer, stacking and compounding in the order of upper layer, middle layer, and lower layer, and hot pressing at a pressure of 0.18 MPa and a temperature of 140° C. for 2.3 h to obtain a flame retardant absorbing material based on expanded polystyrene.
[0028] Example 4 This embodiment discloses a method for preparing a flame retardant wave absorbing material based on foamed polystyrene, comprising the following steps: Step (1), mixing the graphene azidite / ferrous oxide composite material with N,N-dimethylformamide, ultrasonically dispersing for 5 minutes, adding propargyl linear phenolic resin, and then adding ligand pentamethyldiethyltriamine and catalyst cuprous iodide in a nitrogen atmosphere, wherein the mass ratio of the graphene azidite / ferrous oxide composite material, N,N-dimethylformamide, propargyl linear phenolic resin, pentamethyldiethyltriamine, and catalyst cuprous iodide is 1:120:2.95:0.03:0.28, reacting at 30°C for 24 hours, and after the reaction is completed, centrifuging, filtering, taking the filter cake, and drying it at 55°C for 20 hours in a light-proof environment to obtain a wave absorbing agent; The preparation of the graphene azide / ferroferric oxide composite material is the same as that in Example 1; the propargyl linear phenolic resin is prepared by the following steps: Mix the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water and butanone evenly, add the catalyst triethylbenzyl ammonium chloride, the mass ratio of the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water, butanone and the catalyst is 10:3.15:9.15:57:53:0.13, stir and react at 80°C for 8h, after the reaction is completed, obtain a crude reaction product, add water 3 times the mass of the crude reaction product for washing, take the organic phase, remove the solvent by rotary evaporation, and dry at 110°C for 12h to obtain the propargylated linear phenolic resin; Step (2), mixing phenolic resin, flame retardant functionalized phenolic resin, ammonium polyphosphate, and absorber in a mass ratio of 58:42:5.8:24, and stirring at a speed of 400 r / min for 8 minutes to obtain a flame retardant coating resin; The flame retardant functionalized phenolic resin is prepared by the following steps: The preparation of the modified phenolic resin is the same as that in Example 1; the modified phenolic resin and the solvent N,N-dimethylacetamide are mixed and dissolved in a mass ratio of 1:5, 4-nitrophthalonitrile and the catalyst potassium carbonate are added, the mass ratio of the modified phenolic resin, 4-nitrophthalonitrile and the catalyst potassium carbonate is 60:13.5:15.8, and the mixture is reacted at 80°C for 16 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, and the filtrate is taken, and a 0.01 mol / L aqueous solution of hydrogen chloride is added to neutralize the mixture to neutrality to obtain a crude reaction product, and 8 times the mass of butanone of the crude reaction product is added for extraction, and the organic phase is taken, the solvent is removed by rotary evaporation, and the mixture is dried at 55°C for 8 hours to obtain a flame retardant functionalized phenolic resin; Step (3), placing the expandable polystyrene beads in water vapor, pre-foaming them in water vapor with a vapor pressure of 0.5 MPa at a temperature of 100° C. for 55 seconds, and after the pre-foaming is completed, aging them at room temperature for 18 hours to obtain pre-foamed polystyrene beads; The pre-foamed polystyrene beads and the flame-retardant coating resin were mixed and stirred at a mass ratio of 25:17 for 15 minutes, so that the flame-retardant coating resin was evenly coated on the surface of the pre-foamed polystyrene beads, dried at 55°C for 10 minutes, placed in a mold after drying, and secondary foamed for 3 minutes in water vapor with a vapor pressure of 0.4MPa at 130°C. After the secondary foaming, cooled to room temperature, dried at 55°C for 26 hours, and obtained a foamed polystyrene-based composite material with a thickness of 48mm; Step (4), using the expanded polystyrene-based composite material as the middle layer, the glass fiber prepreg as the upper layer, and the carbon fiber material as the lower layer, stacking and compounding in the order of upper layer, middle layer, and lower layer, and hot pressing at a pressure of 0.2 MPa and a temperature of 145° C. for 2 hours to obtain a flame retardant absorbing material based on expanded polystyrene.
[0029] Example 5 This embodiment discloses a method for preparing a flame retardant wave absorbing material based on foamed polystyrene, comprising the following steps: Step (1), mixing the graphene azidite / ferrous oxide composite material with N,N-dimethylformamide, ultrasonically dispersing for 8 minutes, adding propargyl linear phenolic resin, and then adding ligand pentamethyldiethyltriamine and catalyst cuprous iodide in a nitrogen atmosphere, wherein the mass ratio of the graphene azidite / ferrous oxide composite material, N,N-dimethylformamide, propargyl linear phenolic resin, pentamethyldiethyltriamine, and catalyst cuprous iodide is 1:130:3:0.03:0.28, reacting at 30°C for 24 hours, and after the reaction is completed, centrifuging, filtering, taking the filter cake, and drying it at 60°C in a light-proof environment for 18 hours to obtain an absorber; The preparation of the graphene azide / ferroferric oxide composite material is the same as that in Example 1; the propargyl linear phenolic resin is prepared by the following steps: Mix the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water and butanone evenly, add the catalyst triethylbenzyl ammonium chloride, the mass ratio of the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water, butanone and the catalyst is 10:3.2:9.2:60:50:0.14, stir and react at 80°C for 8h, after the reaction is completed, obtain a crude reaction product, add water 4 times the mass of the crude reaction product for washing, take the organic phase, remove the solvent by rotary evaporation, and dry at 120°C for 10h to obtain the propargylated linear phenolic resin; Step (2), mixing phenolic resin, flame retardant functionalized phenolic resin, ammonium polyphosphate, and absorber in a mass ratio of 50:50:6:25, and stirring at a speed of 400 r / min for 10 min to obtain a flame retardant coating resin; The flame retardant functionalized phenolic resin is prepared by the following steps: The preparation of the modified phenolic resin is the same as that in Example 1; the modified phenolic resin and the solvent N,N-dimethylacetamide are mixed and dissolved in a mass ratio of 1:5, 4-nitrophthalonitrile and the catalyst potassium carbonate are added, the mass ratio of the modified phenolic resin, 4-nitrophthalonitrile and the catalyst potassium carbonate is 60:14:16, and the reaction is carried out at 80°C for 16 hours. After the reaction is completed, it is cooled to room temperature, filtered, and the filtrate is taken, and a 0.01 mol / L aqueous solution of hydrogen chloride is added to neutralize it to neutrality to obtain a crude reaction product, and 10 times the mass of butanone of the crude reaction product is added for extraction, and the organic phase is taken, the solvent is removed by rotary evaporation, and it is dried at 60°C for 8 hours to obtain a flame retardant functionalized phenolic resin; Step (3), placing the expandable polystyrene beads in water vapor, pre-foaming them in water vapor with a vapor pressure of 0.5 MPa at a temperature of 100° C. for 55 seconds, and after the pre-foaming is completed, aging them at room temperature for 20 hours to obtain pre-foamed polystyrene beads; The pre-foamed polystyrene beads and the flame-retardant coating resin were mixed and stirred at a mass ratio of 25:18 for 15 minutes, so that the flame-retardant coating resin was evenly coated on the surface of the pre-foamed polystyrene beads, dried at 60°C for 10 minutes, placed in a mold after drying, and secondary foamed for 3 minutes at 130°C in water vapor with a vapor pressure of 0.4MPa. After the secondary foaming, cooled to room temperature, dried at 60°C for 24 hours, and obtained a foamed polystyrene-based composite material with a thickness of 50mm; Step (4), using the expanded polystyrene-based composite material as the middle layer, the glass fiber prepreg as the upper layer, and the carbon fiber material as the lower layer, stacking and compounding in the order of upper layer, middle layer, and lower layer, and hot pressing at a pressure of 0.2 MPa and a temperature of 145° C. for 2 hours to obtain a flame retardant absorbing material based on expanded polystyrene.
[0030] Comparative Example 1 This comparative example discloses a method for preparing a material based on expanded polystyrene, comprising the following steps: Step (1), mixing phenolic resin, flame retardant functionalized phenolic resin, ammonium polyphosphate and graphene in a mass ratio of 60:40:5:5, and stirring at a speed of 400 r / min for 6 minutes to obtain a flame retardant coating resin; The flame retardant functionalized phenolic resin is prepared by the following steps: The preparation of the modified phenolic resin is the same as that in Example 1; the modified phenolic resin and the solvent N,N-dimethylacetamide are mixed and dissolved in a mass ratio of 1:4, 4-nitrophthalonitrile and the catalyst potassium carbonate are added, the mass ratio of the modified phenolic resin, 4-nitrophthalonitrile and the catalyst potassium carbonate is 60:12:15, and the mixture is reacted at 75°C for 18 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, and the filtrate is taken, and a 0.01 mol / L aqueous solution of hydrogen chloride is added to neutralize the mixture to neutrality to obtain a crude reaction product, and 8 times the mass of butanone of the crude reaction product is added for extraction, and the organic phase is taken, the solvent is removed by rotary evaporation, and the mixture is dried at 50°C for 10 hours to obtain a flame retardant functionalized phenolic resin; Step (3), placing the expandable polystyrene beads in water vapor, pre-foaming them in water vapor with a vapor pressure of 0.4 MPa at a temperature of 100° C. for 50 seconds, and after the pre-foaming is completed, aging them at room temperature for 12 hours to obtain pre-foamed polystyrene beads; The pre-foamed polystyrene beads and the flame-retardant coating resin were mixed and stirred at a mass ratio of 25:15 for 10 minutes, so that the flame-retardant coating resin was evenly coated on the surface of the pre-foamed polystyrene beads, dried at 50°C for 15 minutes, placed in a mold after drying, and secondary foamed for 3.5 minutes at 120°C in water vapor with a vapor pressure of 0.3MPa. After the secondary foaming, cooled to room temperature, dried at 50°C for 30 hours, and obtained a foamed polystyrene-based composite material with a thickness of 40mm; Step (4), using the expanded polystyrene-based composite material as the middle layer, the glass fiber prepreg as the upper layer, and the carbon fiber material as the lower layer, stacking and compounding in the order of upper layer, middle layer, and lower layer, and hot pressing at a pressure of 0.15 MPa and a temperature of 135° C. for 2.5 hours to obtain a material based on expanded polystyrene.
[0031] Comparative Example 2 This comparative example discloses a method for preparing a material based on expanded polystyrene, comprising the following steps: Step (1), mixing the graphene azidite / ferrous oxide composite material with N,N-dimethylformamide, ultrasonically dispersing for 5 minutes, adding propargyl linear phenolic resin, and then adding ligand pentamethyldiethyltriamine and catalyst cuprous iodide in a nitrogen atmosphere, wherein the mass ratio of the graphene azidite / ferrous oxide composite material, N,N-dimethylformamide, propargyl linear phenolic resin, pentamethyldiethyltriamine, and catalyst cuprous iodide is 1:100:2.8:0.03:0.28, reacting at 25°C for 26 hours, and after the reaction is completed, centrifuging, filtering, taking the filter cake, and drying it at 50°C for 24 hours in a light-proof environment to obtain a wave absorbing agent; The preparation of the graphene azide / ferroferric oxide composite material is the same as that in Example 1; the propargyl linear phenolic resin is prepared by the following steps: Mix the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water and butanone evenly, add the catalyst triethylbenzyl ammonium chloride, the mass ratio of the linear phenolic resin, sodium hydroxide, 3-bromopropyne, water, butanone and the catalyst is 10:3:9:50:60:0.1, stir and react at 70°C for 10h, after the reaction is completed, obtain a crude reaction product, add water 3 times the mass of the crude reaction product for washing, take the organic phase, remove the solvent by rotary evaporation, and dry at 100°C for 14h to obtain the propargylated linear phenolic resin; Step (2), mixing phenolic resin, ammonium polyphosphate and absorber in a mass ratio of 100:40:5:20, stirring at a speed of 400 r / min for 6 minutes, to obtain a flame retardant coating resin; Step (3), placing the expandable polystyrene beads in water vapor, pre-foaming them in water vapor with a vapor pressure of 0.4 MPa at a temperature of 100° C. for 50 seconds, and after the pre-foaming is completed, aging them at room temperature for 12 hours to obtain pre-foamed polystyrene beads; The pre-foamed polystyrene beads and the flame-retardant coating resin were mixed and stirred at a mass ratio of 25:15 for 10 minutes, so that the flame-retardant coating resin was evenly coated on the surface of the pre-foamed polystyrene beads, dried at 50°C for 15 minutes, placed in a mold after drying, and secondary foamed for 3.5 minutes at 120°C in water vapor with a vapor pressure of 0.3MPa. After the secondary foaming, cooled to room temperature, dried at 50°C for 30 hours, and obtained a foamed polystyrene-based composite material with a thickness of 40mm; Step (4), using the expanded polystyrene-based composite material as the middle layer, the glass fiber prepreg as the upper layer, and the carbon fiber material as the lower layer, stacking and compounding in the order of upper layer, middle layer, and lower layer, and hot pressing at a pressure of 0.15 MPa and a temperature of 135° C. for 2.5 hours to obtain a material based on expanded polystyrene.
[0032] In the above embodiments and comparative examples: The carbon fiber material is homemade and is prepared by the following steps: five layers of carbon fiber cloth are laminated and composited, epoxy resin is brushed on the carbon fiber cloth and rolled, the mass ratio of carbon fiber cloth to epoxy resin is 3:2, hot pressing at 100°C for 50min, heating to 140°C, and hot pressing at a pressure of 15MPa for 2h, and then cutting to obtain the carbon fiber material; Among them, the epoxy resin is prepared by mixing epoxy resin E51, curing agent hexahydrophthalic anhydride (HHPA), and accelerator 2,4,6-tris(dimethylaminomethyl)phenol in a mass ratio of 100:80:0.2; the carbon fiber cloth is T700 carbon fiber cloth, the specification is plain cloth, from Weihai Guangwei Composite Materials Co., Ltd., item number TZ700S.
[0033] The glass fiber prepreg comes from Changzhou Xingao Insulation Materials Co., Ltd., item number WL-300A, with a plain weave, a gram weight of 308g / m2, and a resin content of 30-40%; graphene comes from McLean Biochemical Technology Co., Ltd., with a thickness of 1-10 layers and an average radial size of 5-10μm, item number G762016; 3-(azidopropyl)triethoxysilane comes from MacLean Biochemical Technology Co., Ltd., CAS No.: 83315-69-9; linear phenolic resin comes from Green Union Chemical Technology Co., Ltd., with an average molecular weight of 420; phenolic resin comes from Shandong Jining Huakai Resin Co., Ltd., with the item number PF-3213; ammonium polyphosphate comes from West Asia Chemical Co., Ltd., with the item number B20370; hexa(p-aminophenoxy)cyclotriphosphazene comes from Jiangsu Aikon Biomedicine Research and Development Co., Ltd., CAS No.: 13441-26-4; 4-nitrophthalonitrile comes from Aladdin Biochemical Technology Co., Ltd., CAS No.: 31643-49-9; expandable polystyrene beads come from Shenghao Plastic Raw Materials Co., Ltd., brand 301H, particle size 0.3-0.5mm.
[0034] Test example (1) Impact resistance and flame retardancy test The expanded polystyrene-based composite materials prepared in Examples 1-5 and Comparative Examples 1-2 were respectively recorded as Samples 1-7. The impact resistance and flame retardancy of Samples 1-7 were tested. The specific test results are shown in Table 1: Table 1
[0035] The testing of the indicators in Table 1 is based on the following standards: the limiting oxygen index is measured with reference to GB / T2406.1-2008 "Determination of Combustion Behavior of Plastics by Oxygen Index Method"; the impact strength is measured with reference to GB / T1043-93 "Determination of Impact Properties of Plastic Simply Supported Beams".
[0036] It can be seen from the test results in Table 1 that among the materials based on expanded polystyrene prepared by the present invention, the expanded polystyrene-based composite material has excellent flame retardancy and good impact resistance.
[0037] In Comparative Example 2, no flame retardant functional phenolic resin is added, and the flame retardant structure of cyclotriphosphazene and the flame retardant and heat-resistant phthalonitrile structure are lacking to improve the flame retardant properties of the material. Therefore, the flame retardant properties of Comparative Example 2 are lower than those of the embodiment.
[0038] (2) Wave absorption performance test The wave absorbing properties of the expanded polystyrene-based materials prepared in Examples 1-5 and Comparative Examples 1-2 were tested, and the specific test results are shown in Table 2: Table 2
[0039] The detection of the indicators in Table 1 is based on the following standards: The absorbing performance is represented by reflectivity, which is measured with reference to GJB 2038A-2011 "Test Method for Reflectivity of Radar Absorbing Materials", and the test frequency band is 8-18 GHz.
[0040] It can be seen from the test results in Table 2 that the expanded polystyrene-based material prepared in the present invention has excellent wave absorbing performance.
[0041] The composite of the magnetic loss type absorbing material ferroferric oxide and the resistive loss type absorbing material graphene helps to improve impedance matching and allow more electromagnetic waves to enter the absorbing material. In Comparative Example 1, only graphene is used as the absorbing material, and the magnetic material ferroferric oxide and graphene are lacking to synergistically improve the absorbing performance of the material, so the absorbing performance of Comparative Example 1 is not as good as that of the embodiment.
[0042] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a flame retardant absorbing material based on expanded polystyrene, characterized in that: The following steps are involved: Step (1), mixing the graphene azide / ferroferric oxide composite material with N,N-dimethylformamide, ultrasonically dispersing, adding propargyl linear phenolic resin, and then adding pentamethyldiethyltriamine and cuprous iodide in a nitrogen atmosphere, reacting, and after the reaction is completed, centrifuging, filtering, and drying to obtain a wave absorbing agent; Step (2), pre-foaming the expandable polystyrene beads, and after the pre-foaming is completed, aging to obtain pre-foamed polystyrene beads; The pre-foamed polystyrene beads are mixed with a flame-retardant coating resin, stirred, dried, placed in a mold after drying, and foamed a second time. After the second foaming is completed, cooled and dried to obtain a foamed polystyrene-based composite material; The flame retardant coating resin is prepared by the following steps: mixing phenolic resin, flame retardant functionalized phenolic resin, ammonium polyphosphate and a wave absorbing agent to obtain the flame retardant coating resin; Step (3), using the expanded polystyrene-based composite material as the middle layer, compounding it with the upper layer and the lower layer, and hot pressing it to obtain a flame-retardant absorbing material based on expanded polystyrene.
2. The method for preparing a flame retardant absorbing material based on expanded polystyrene according to claim 1, characterized in that: The azide graphene / ferroferric oxide composite material in step (1) is prepared by the following steps: The graphene, ferric chloride hexahydrate, sodium acetate and a solvent are mixed, ultrasonically dispersed, reacted, and after the reaction is completed, cooled, centrifuged, filtered, washed and dried to obtain a graphene / ferrosoferric oxide composite material; The mass ratio of graphene, ferric chloride hexahydrate, sodium acetate and solvent is 0.03:2-2.1:37.5-38:835; the reaction conditions are: reacting at 200°C for 8-10 hours; The 3-(azidopropyl)triethoxysilane, the graphene / ferroferric oxide composite material and toluene are mixed and reacted, and after the reaction is completed, the mixture is filtered, washed and dried to obtain the azido graphene / ferroferric oxide composite material; The mass ratio of 3-(azidopropyl)triethoxysilane, graphene / ferroferric oxide composite material and toluene is 0.18-0.2:0.1:100-130; the reaction conditions are: reacting at 70-80°C for 24-30h in a light-proof environment.
3. The method for preparing a flame retardant absorbing material based on expanded polystyrene according to claim 1, characterized in that: The propargyl phenolic resin in step (1) is prepared by the following steps: The linear phenolic resin, sodium hydroxide, 3-bromopropyne, water and butanone are uniformly mixed, a catalyst is added, and the mixture is reacted. After the reaction is completed, the mixture is purified to obtain the propargylated linear phenolic resin. The mass ratio of linear phenolic resin, sodium hydroxide, 3-bromopropyne, water, butanone and catalyst is 10:3-3.2:9-9.2:50-60:50-60:0.1-0.14; the reaction conditions are: stirring the reaction at 70-80°C for 8-10 hours.
4. The method for preparing a flame retardant absorbing material based on expanded polystyrene according to claim 1, characterized in that: In the step (1), the mass ratio of the graphene azide / ferroferric oxide composite material, N,N-dimethylformamide, propargyl linear phenolic resin, pentamethyldiethyltriamine, and cuprous iodide is 1:100-130:2.8-3:0.03:0.28; and the reaction conditions are: reacting at a temperature of 25-30° C. for 24-26 hours.
5. The method for preparing a flame retardant absorbing material based on expanded polystyrene according to claim 1, characterized in that: In the step (2), the pre-foaming conditions are: pre-foaming in water vapor with a vapor pressure of 0.4-0.5 MPa and a temperature of 100°C for 50-55 seconds; the aging conditions are: aging at room temperature for 12-20 hours; the mass ratio of the pre-foamed polystyrene beads to the flame-retardant coating resin is 25:15-18; the secondary foaming conditions are: secondary foaming in water vapor with a vapor pressure of 0.3-0.4 MPa and a temperature of 120-130°C for 3-3.5 minutes; and the thickness of the foamed polystyrene-based composite material is 40-50 mm.
6. The method for preparing a flame retardant absorbing material based on expanded polystyrene according to claim 1, characterized in that: When preparing the flame-retardant coating resin in step (2), the mass ratio of phenolic resin, flame-retardant functionalized phenolic resin, ammonium polyphosphate and absorber is 50-60:40-50:5-6:20-25.
7. The method for preparing a flame retardant absorbing material based on expanded polystyrene according to claim 6, characterized in that: When preparing the flame-retardant coating resin in step (2), the flame-retardant functionalized phenolic resin is prepared by the following steps: S11, mixing phenol, sodium hydroxide, the first portion of paraformaldehyde, and water, adding hexa(p-aminophenoxy)cyclotriphosphazene, reacting, adding the second portion of paraformaldehyde after the reaction is completed, continuing the reaction, adding the third portion of paraformaldehyde after the reaction is completed, reacting again, and cooling to room temperature after the reaction is completed to obtain a modified phenolic resin; S12, mixing and dissolving the modified phenolic resin and N,N-dimethylacetamide, adding 4-nitrophthalonitrile and a catalyst potassium carbonate, reacting, cooling after the reaction, purifying, and obtaining a flame-retardant functionalized phenolic resin.
8. The method for preparing a flame retardant wave absorbing material based on expanded polystyrene according to claim 7, characterized in that: When preparing the flame retardant functionalized phenolic resin: In S11, the mass ratio of phenol, sodium hydroxide, water, paraformaldehyde and hexa(p-aminophenoxy)cyclotriphosphazene is 92-94:0.4-0.5:6:40-46:8-10; the paraformaldehyde includes the first paraformaldehyde, the second paraformaldehyde and the third paraformaldehyde, and the mass ratio of the first paraformaldehyde, the second paraformaldehyde and the third paraformaldehyde is 1:1:1; the reaction conditions are: react at 80-90°C for 1-2h, continue to react at 80-90°C for 0.5-1h, and react again at 80-90°C for 1-1.5h; In S12: the mass ratio of modified phenolic resin, 4-nitrophthalonitrile and catalyst potassium carbonate is 60:12-14:15-16; the reaction conditions are: react at a temperature of 75-80°C for 16-18h.
9. The method for preparing a flame retardant wave absorbing material based on expanded polystyrene according to claim 1, characterized in that: In the step (3), the upper layer is glass fiber prepreg, the lower layer is carbon fiber material, and the hot pressing conditions are: hot pressing at a pressure of 0.15-0.2 MPa and a temperature of 135-145° C. for 2-2.5 hours.
10. A flame retardant absorbing material based on expanded polystyrene prepared by the method for preparing a flame retardant absorbing material based on expanded polystyrene according to any one of claims 1 to 9.
Citation Information
Patent Citations
Wave-absorbing honeycomb core material and wave-absorbing honeycomb core sandwich structure
CN114670526A
Nano composite absorbing material and preparation method thereof
CN105950112A
Method for preparing cyclotriphosphazene-modified phenolic resin
CN106397700A
Graphene graft modified phenolic resin material and preparation method thereof
CN108102290A
Wave-absorbing composite material as well as preparation method and application thereof
CN113337044A
Cited By
Flame-retardant antibacterial wave-absorbing PET (Polyethylene Terephthalate) fiber and preparation method thereof
CN120683631A
High-strength composite film, preparation process and application of high-strength composite film in power battery
CN122427396A